STUDI KESULITAN MAHASISWA DALAM MEMPELAJARI DERET TAK HINGGA : STUDI KASUS DI JURUSAN MATEMATIKA UNIMED - Rahmadani, Nisa; Aulia, Cut Najwa; Laia, Lukman Hakim; Maigani, Maigani; Simanullang, Michael Christian (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
infinite series is an important concept in mathematics which often becomes a challenge for students. This study aims to analyze the difficulties faced by students of the Mathematics Department at Medan State University (UNIMED) in understanding and solving problems related to infinite series. This research uses a survey method with a questionnaire given to students who have studied this material. The research results show that the students' main difficulties lie in understanding the concept of convergence, using the convergence test, and applying it in problem solving. Based on the research results, it is recommended that there is a more interactive and technology-based learning approach to increase student understanding